Relapsing Polychondritis: A Case Report of the Use of Adalimumab in Steroid Dependent Disease - Dimmerling, Taylor; Altattan, Mohamed; Altorok, Nezam (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.